Answer:
(f circle g )(x ) = f(g(x)) = 12(3x) = 36x
(f circle g )(x ) computes the number of inches in x yards
Explanation:
Data provided in the question;
f(x) = 12x [here f(x) computes the number of inches in x feet ]
and,
g(x) = 3x [ here g(x) computes the number of feet in x yards ]
now,
(f circle g )(x ) represents f(g(x)) i,e the result of the function g(x) is input for the function f(x)
thus,
(f circle g )(x ) = f(g(x)) = 12(3x) = 36x
This function computes the number of inches where x is in yards
thus,
(f circle g )(x ) computes the number of inches in x yards